2013
DOI: 10.1007/978-1-4614-6093-0_5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long-Term Taurine Supplementation and Fructose Feeding on Glucose and Lipid Homeostasis in Wistar Rats

Abstract: The nonprotein amino acid taurine has been shown to counteract the negative effects of a high-fructose diet in rats with regard to insulin resistance and dyslipidemia. Here we examined the long-term (26 weeks) effects of oral taurine supplementation (2% in the drinking water) in fructose-fed Wistar rats.The combination of fructose and taurine caused a significant increase in fasting glucose compared to the control diet without changing hepatic phosphoenol pyruvate carboxykinase mRNA levels. The combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We have shown that taurine (2% in drinking water) can reverse the adverse metabolic effects in mother and offspring associated with a high fat : high fructose intake and also have data that maternal hyperinsulinemia associated with fructose intake is normalised with taurine supplementation [91]. However, as reported by Larsen et al, the combination of taurine and fructose can also increase fasting glucose levels in certain experimental models, therefore suggesting that the beneficial effect of taurine supplementation towards amelioration of glucose intolerance and insulin resistance may be dependent upon the dose and duration of fructose intake [92]. …”
Section: Countering the Adverse Metabolic Effects Of Fructosementioning
confidence: 99%
“…We have shown that taurine (2% in drinking water) can reverse the adverse metabolic effects in mother and offspring associated with a high fat : high fructose intake and also have data that maternal hyperinsulinemia associated with fructose intake is normalised with taurine supplementation [91]. However, as reported by Larsen et al, the combination of taurine and fructose can also increase fasting glucose levels in certain experimental models, therefore suggesting that the beneficial effect of taurine supplementation towards amelioration of glucose intolerance and insulin resistance may be dependent upon the dose and duration of fructose intake [92]. …”
Section: Countering the Adverse Metabolic Effects Of Fructosementioning
confidence: 99%
“…Fructose feeding is an established experimental model for inducing the metabolic syndrome in rats [ 10 , 11 ]; however, studies vary significantly in fructose delivery and the administered concentration. The concentration of fructose administered as a component of chow itself is generally supraphysiological and ranges between 60%–70% w / w or 0.6–0.7 g/g chow [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], whereas the concentration of fructose beverages can often vary anywhere between 10%–30% w / v or 0.1–0.3 g fructose/mL water [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Despite the reported effects on metabolic health, studies investigating the effect of high concentrations of fructose in chow or as a beverage report no effect of fructose consumption on rodent body weight [ 10 , 12 , 46 , 47 ], while others report an increase in body weight [ 22 , 23 , 27 , 29 , ...…”
Section: Introductionmentioning
confidence: 99%
“…However, taurine supplementation alone signifi cantly increased fasting glucose levels (Table 2 ), which is inconsistent with previous fi ndings showing that taurine improves insulin sensitivity and reduces hyperglycemia (Nandhini and Anuradha 2003 ;Nandhini et al 2005a ). Recently we reported an increase in fasting glucose after 26 weeks of taurine supplementation in male Wistar rats (Larsen et al 2013 ). Sub-strain differences in the outbred Wistar rat strain is a possible explanation, as there seem to be some rat strain differences in the response to fructose (Stark et al 2000 ).…”
Section: Body and Plasma Parametersmentioning
confidence: 96%
“…RNA was extracted from different tissues using Qiazol (Qiagen, Valencia, CA, USA) as described earlier (Larsen et al 2013 ). Total RNA was mixed (at a concentration > 0.15 μg/μl for a total of 2 μg RNA in 20 μl volume) with reverse transcriptase, random hexamer primers and nucleotides and cDNA synthesis performed using the High Capacity cDNA Reverse Transcription Kit with RNase inhibitor (Applied Biosystems, Carlsbad, CA, USA) as described earlier (Larsen et al 2013 ) Amplifi cation mixtures were amplifi ed using a SYBR Green mastermix (Applied Biosystems) according to standard conditions ((95 °C 10 min) × 1, (95 °C 15 s, 60 °C 1 min, 95 °C 15 s, 60 °C 15 s, 95 °C 15 s) × 50 cycles in a total volume of 10 μl with a melting curve from 60 to 100 °C) in 384 well plates in triplicates on an ABI VIIA7 real-time PCR system (Applied Biosystems).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%